Hubungan Self Efficacy dengan Kecemasan pada Pasien Pre Operasi Menggunakan Metode Anestesi Spinal di RSUD Kardinah Kota Tegal - Riyan Makhfudin; Wilis Sukmaningtyas; Wasis Eko Kurniawan (Seminar Nasional Penelitian dan Pengabdian Kepada Masyarakat, 2023)
Self efficacy is a belief, a person's ability to manage situations when anxious, threatened or otherwise. Anxiety in preoperative patients is associated with psychology, lack of sleep, restlessness, lethargy, crying easily and sleep deprivation. The purpose of this thesis is to determine the relationship between Self efficacy and anxiety in preoperative patients using the spinal anesthesia method at Kardinah General Hospital, Tegal City. This research uses quantitative observational analytic research with a cross sectional design. This research was conducted at the Kardinah Hospital in Tegal City from October 1 to 31 2022. The number of samples in this study were 44 respondents who were taken using the consecutive sampling technique. The instrument used in this research is a questionnaire. The results showed that respondents with low self efficacy (59.09%) and the anxiety level of respondents were in the severe anxiety category (54.54%). The results of the correlation coefficient r product is 0.929 greater than r table which is 0.297 with a significant correlation coefficient of 0.000. From the results of the study it was found that there was a relationship between self efficacy and anxiety in preoperative patients with spinal anesthesia at Kardinah Regional General Hospital, Tegal City.